PROCESSING OF FISHERY WASTE AS AN ALTERNATIVE SOURCE OF GELATIN PRODUCTION - Sari, Femiliani Novita; Nur, Widya; Surianti, Surianti; Nurliana, Nurliana; Mawar, Ida (Jurnal Perikanan Unram, 2025)
The Indonesian industry still relies heavily on gelatin imports from countries such as Brazil, India, China, Thailand, and the United States. Unfortunately, the majority of this imported gelatin is made from pigskin, which is haram for Muslims, the majority of Indonesia's population. The use of fish waste for gelatin production is rooted in the need to maximize the utilization of fishery resources and reduce the environmental impact of fishing industry waste. The fishing industry produces abundant waste, mainly in the form of fish bones, skin and scales. Gelatin is widely used for glue manufacturing, cosmetic products, emulsifiers in the food industry, and pharmaceutical products. Gelatin from fish scales can be used as a formulation ingredient in food products such as syrup thickeners, jelly candy, confectionery, ice cream and noodle chewers.